Questionnaire Survey of Bowel Habit in Japanese Medical Personnel - Kotaro Maeda; Yoshikazu Koide; Hidetoshi Katsuno; Tsunekazu Hanai; Koji Masumori; Hiroshi Matsuoka; Tomoyoshi Endo; Yeong Cheol Cheong (Journal of the Anus, Rectum and Colon, 2021)
Objectives: This study aims to clarify the bowel habit, change of bowel movement throughout the cycle of menstruation, and toilet use in Japanese medical personnel. Methods: A questionnaire survey was completed by Japanese medical personnel after listening to lectures on bowel disorders. Constipation was defined according to Rome III criteria, whereas diarrhea was defined as Bristol stool form scale type 6 and 7. Results: In total, 463 persons (mean age, 35.6 years, range 20-91, male/female/no answer: 132/324/7) have completed the questionnaire. Constipation was significantly more often observed in females (male/female: 3%/31%, p > 0.001, Chi-squared test), while diarrhea was noted to be less in females (male/female: 1%/7%). Constipation was observed in 20% of participants in their 20s, and the constipation rate was observed to gradually increase with age. It was observed in 45% of participants in their 70s or older. Bowel movement changed to constipation around menstruation in 18% of females and changed to diarrhea in 43% of females. Constipation often occurred before menstruation and diarrhea during menstruation. Only 2% of participants used a Japanese-style toilet, and 5% of participants claimed that they were unable to pass a stool on a Japanese-style toilet. Conclusions: Constipation was significantly more frequent in females and increased with age among female Japanese medical personnel. Change of bowel movement occurred in 61% of females around menstruation. Five percent of participants were unable to pass stools on a Japanese-style toilet.